Assessment of poliovirus antibody seroprevalence in polio high risk areas of West Africa. Issue 8 (14th February 2018) - Guindo, Oumar; Mach, Ondrej; Doumbia, Seydou; Ekra, Daniel K.; Beavogui, Abdoul H.; Weldon, William C.; Oberste, M. Steven; Sutter, Roland W.
Abstract: We conducted a serological survey of anti-polio antibodies in polio high-risk areas of Mali, Guinea and Cote d'Ivoire to assess risk of future poliovirus outbreaks. Random community sampling of children 6–11 and 36–48 months-old was conducted; neutralizing antibodies against poliovirus were detected using microneutralization assay. We analysed 1059/1064 (99.5%) of enrolled children. Seroprevalence to poliovirus type 1 (PV1) across all age groups and locations ranged between 92 and 100%, for PV2 it was 77–100%, and 89–95% for PV3. PV2 seroprevalence in the younger age group in Guinea and Cote d'Ivoire was <80%. History of <4 polio vaccine doses and acute malnutrition were associated with seronegativity (OR = 2.1 CI95% = 1.5–3.1, OR = 1.8 CI95% = 1.1–3.3 respectively). The risk of poliovirus outbreak following importation is low because of high population immunity to PV1, however, due to large cohort of PV2 seronegative children any future detection of vaccine-derived poliovirus type 2 requires urgent response to arrest rapid spread.